A digital media attention diversion improves mood and fear in patients receiving chemotherapy for recurrent gynecologic malignancies: results of a randomized trial. Issue 4 (1st March 2020) - Spencer, Ryan; Alexander, Vinita; Eickhoff, Jens; Woo, Kaitlin; Costanzo, Erin; Marx, Nick; Rose, Stephen
Abstract : Background: Recurrent gynecologic cancer patients experience symptoms that affect psychologic, emotional, social, and physical well-being. Chemotherapy can further exacerbate these symptoms. Poor mood, pain, and fatigue are linked and are detrimental to quality of life. Interventions targeting these symptoms may improve patient-reported outcomes and performance status. Objectives: To determine the ability of a humorous digital media attention diversion to improve symptom domains of positive and negative mood during chemotherapy for patients with recurrent gynecologic cancers. Study design: This randomized, crossover clinical trial enrolled women with recurrent gynecologic cancers. Subjects participated over three cycles of chemotherapy. The primary outcome was the change in mood on the validated Positive and Negative Affect Scale-Extended (PANAS-X) instrument, which measures positive and negative affect domains. All subjects completed the PANAS-X after receiving chemotherapy during cycle 1 on study. In atudy arm 1, subjects watched their choice of humorous movies on a digital media device while receiving chemotherapy during cycle 2 on study. They selected from non-humorous movies during cycle 3 on study. In arm 2, the order of movies was reversed. After each cycle, mood, fatigue, and other patient-reported outcomes were assessed for comparison with baseline measurements. Results: The target enrollment of 66 subjects was achieved. Subjects watched humorous content for an average of 96.0 min and non-humorous content for an average of 62.5 min. Negative mood improved after exposure to humorous (p=0.017) and non-humorous content (p=0.001). Patient-reported fear also improved after exposure to both humorous (p=0.038) and non-humorous content (p=0.002). Subjects reported higher use of affiliating and self-effacing humor types. Conclusions: Offering patients a choice of digital media during chemotherapy significantly improved negative mood and fear. This was seen with both humorous and non-humorous content. This low-cost and low-risk intervention should be implemented as an attention diversion to improve negative mood and fear for patients receiving chemotherapy.